1997
DOI: 10.1002/hep.510260406
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide and oxygenation abnormalities in hepatic cirrhosis

Abstract: Impaired arterial oxygenation, ranging from increased alImpaired arterial oxygenation, ranging from increased alveolar-arterial oxygen gradient (AaDo 2 ) to hypoxemia, is veolar-arterial oxygen gradient (AaDo 2 ) to hypoxemia, is comcommonly reported in patients with cirrhosis. 1 In the absence monly present in patients with cirrhosis. Nitric oxide (NO), of overt mechanical dysfunction of the lung, it has been through pulmonary vasodilatation, may play a major role in suggested that oxygenation abnormalities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(56 citation statements)
references
References 6 publications
3
49
0
3
Order By: Relevance
“…Increased production of the gaseous vasodilators nitric oxide and carbon monoxide has also been associated with vascular dilatation in HPS,30,44,45 and, thus, we tested variants in the inducible and endothelial forms of nitric oxide synthase (NOS) as well as heme oxygenase 1 ( HMOX1 ), the rate-limiting enzyme in the production of carbon monoxide. A recent report found that the Glu298Asp (rs1799983) variant in NOS3 was associated with risk of HPS in 20 subjects with pediatric (predominately anatomic or metabolic) liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Increased production of the gaseous vasodilators nitric oxide and carbon monoxide has also been associated with vascular dilatation in HPS,30,44,45 and, thus, we tested variants in the inducible and endothelial forms of nitric oxide synthase (NOS) as well as heme oxygenase 1 ( HMOX1 ), the rate-limiting enzyme in the production of carbon monoxide. A recent report found that the Glu298Asp (rs1799983) variant in NOS3 was associated with risk of HPS in 20 subjects with pediatric (predominately anatomic or metabolic) liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the contrast agent used may have contributed to the different prevalence data. Krowka and colleagues 7 and Stoller and colleagues 13 in part used indocyanine green dye solution which provides microbubbles with diameters of up to 90 µm, while we and others (Hopkins and colleagues, 8 Abrams and colleagues, 5 Rolla and colleagues, 15 and Aller and colleagues 6 ) used saline solution which creates microbubbles of 15-180 µm. Vedrinne and colleagues 10 used a modified fluid gelatine solution which creates microbubbles of 10±2 µm.…”
Section: Discussionmentioning
confidence: 99%
“…The crucial role of NO pathway has been suggested in the development of HPS in experimental and human studies. Cirrhotic patients with HPS have higher levels of exhaled NO compared to cirrhotic patients without HPS [10]. NOS isoforms are upregulated in rat model of cirrhosis with HPS [11].…”
Section: Resultsmentioning
confidence: 99%